Illusory Streaks from Corners and Their Perceptual Integration - Roncato, Sergio; Guidi, Stefano; Parlangeli, Oronzo; Battaglini, Luca (Frontiers in Psychology, 2016)
Perceptual grouping appears both as organized forms of real figural units and as illusory or “phantom” figures. The phenomenon is visible in the Hermann grid and in configurations which generate color spreading, e.g., “neon effects”. These configurations, generally regular repetitive patterns, appear to be crossed by illusory bands filled with a brighter shade or a colored tinge connecting the various loci of illusory effects. In this work, we explore a particular new illusion showing a grouping effect. It manifests as illusory streaks irradiating from the vertexes of angular contours and connecting pairs of figures nearby. It is only clearly visible when more than one figure is shown, and takes the shape of a net crossing their corners. Although the grouping effect is vivid, the local source of the illusion is completely hidden. Theories explaining this effect as due to the irradiation of illusory streaks (mainly that of Grossberg and Mingolla, 1985a,b) do not fully explain the figural patterns presented here. Illusory effects have already been documented at the angles of various figures, causing them to alter in amplitude and brightness; however, the figure illustrated here appears to have different features and location. Phenomenological observations and an experiment were conducted to assess the role played by geometric and photometric parameters in this illusion. Results showed that sharp angles, in low contrast with the surround, are the main source of the illusion which, however, only becomes visible when at least two figures are close together. These findings are discussed with respect to theories of contour processing and perceptual grouping, and in relation to other illusions.